An Assessment of Skin Diseases in People and Their Quality of Life in Bundelkhand Region of Uttar Pradesh - Kumar, Manish; Singh, Shilpi; Barman, Seema; Singh, Lal D; Kumar, Navin; Barman, Santosh K (Indian Journal of Community Health, 2023)
Background: Skin diseases occur in all age groups in developed and developing countries. Various types of skin diseases are found worldwide and depend on factors like environment, surrounding ecology, dietary habits, socioeconomic status, mental health, and literacy. Health-related quality of life (HRQOL) improves after treatment or cure of the diseases. Objectives: To estimate the pattern of skin disease. To find out the quality of life and association of skin disease with sociodemographic factors among patients. Methods: This observational cross-sectional study was done in skin OPD at the tertiary care center, Banda district of Uttar Pradesh, India from May 2022 to July 2022. All patients who attended to skin OPD during study period were included in the study after taking informed verbal consent. Results: Skin diseases had further divided in subcategories which were infectious conditions, pigmentary disorders, inflammatory dermatoses, miscellaneous skin conditions, benign tumor and other lesions with their percentage 44.8, 10.5, 28.6, 7.1, 2.9 and 6.2%, respectively in this study Classes of DQLI where major portion of patients (49.52%) were in ‘Small effect on patient’s life’ category. The relation of age, religion, education and member of household with history of skin disease were found to be highly statistically significant. Conclusion: Infectious skin diseases were found more common in study area. Male populations were more commonly affected. Skin diseases were more common in age group of 18–60 years. Study participants showed no predominant effect on quality of life. But small effect class had major effect on participant’s quality of life.